KARAKTERISTIK KOMPOSIT BIOPLASTIK DALAM VARIASI RASIO MAIZENA-GLUKOMANAN DAN VARIASI pH PELARUT - Situmorang, Boy Darwin; Harsojuwono, Bambang Admadi; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): September, 2019)
The purpose of this research is 1) to know the influence of the variation  ratio of cornstarch-glucomannan and variation in solvent conditions to the characteristics of bioplastics, 2) to find out how the variation ratio of cornstarch-glucomannan and variation in pH of solvent that produce bioplastic composites with the best characteristics. This research uses factorial random block designs with 2 factors. Factor I is a variation  ratio of cornstarch-glucomannan consisting 5:1,  4.5:1.5, 4:2. Factor II is a variation in pH of solvent consisting of 3 levels of pH 5, pH 7 and pH 9. Each treatment combination is grouped into 2 based on time of the bioplastic composites making process, so that are 18 experimental units. The data obtained were analyzed of variant and continued with the BNJ (Beda Nyata Jujur) test. The observed variables include mechanical test consisting of tensile strength, elongation of break and modulus young test, biodegradation test, swelling and FTIR. The results showed that the interaction of ratio cornstarch-glucomannan and pH of solvent had a very significant effect on tensile strength, elongation at break and modulus young. In the biodegradation test, pH of solvent had very significant effect on the duration of degradation. While, ini the swelling test, ratio cornstarch-glucomannan had a significant effect on power swelling. Ratio cornstarch-glucomannan (4.5:1.5) at pH 5 in solvents produces the best characteristics of bioplastic composites. Tensile strength 3.04 MPa, elongation at break 18%, modulus Young 16.89 MPa, duration of degradation 5 days and percent of volumen swelling 64.08%. Bioplastic composites contain hiroxyl (O-H), Amines (N-H), Alkynes (C? C), Gugus carboxyl (-COOH), Alkanes (C-H), Amines (C-N), Alcohol (C-O) dan Alkene (C=C). Keywords : Bioplastic Composites, Ratio of Cornstarch-Glucomannan, pH of Solvent